2016
DOI: 10.1111/epp.12306
|View full text |Cite
|
Sign up to set email alerts
|

The EFSA assessment of Trichilogaster acaciaelongifoliae as biocontrol agent of the invasive alien plant Acacia longifolia: a new area of activity for the EFSA Plant Health Panel?

Abstract: This paper summarizes the first assessment by the European Food Safety Authority (EFSA) Plant Health (PLH) Panel of a biological control agent (BCA) of an invasive plant. This followed a request by the European Union (EU) Commission to assess the risk to plant health in the EU of an intentional release of the bud‐galling wasp Trichilogaster acaciaelongifoliae for the control of Acacia longifolia. The EFSA PLH Panel also published a statement on the process of assessing the risk of the intentional releases of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In Portugal, T. acaciaelongifoliae was recently introduced and tested on A. longifolia under controlled conditions with positive results (Marchante et al 2011c). Subsequently, the European Commission (EC), after approval by the EFSA Panel on Plant Health (EFSA 2015;Jeger et al 2016), authorised field tests that were conducted in late 2015 (Shaw et al 2016). First reports indicated that T. acaciaelongifoliae successfully completed its life cycle in Portugal although the number of detected galls is currently low (Marchante et al 2017).…”
Section: Biological Controlmentioning
confidence: 99%
“…In Portugal, T. acaciaelongifoliae was recently introduced and tested on A. longifolia under controlled conditions with positive results (Marchante et al 2011c). Subsequently, the European Commission (EC), after approval by the EFSA Panel on Plant Health (EFSA 2015;Jeger et al 2016), authorised field tests that were conducted in late 2015 (Shaw et al 2016). First reports indicated that T. acaciaelongifoliae successfully completed its life cycle in Portugal although the number of detected galls is currently low (Marchante et al 2017).…”
Section: Biological Controlmentioning
confidence: 99%
“…For the first time, an application was recently referred for an Opinion to the Plant Health Panel of the EFSA. Their report of how this application was assessed offers a possible model for such applications in the future (Jeger et al ., , this issue pages 270–274). The Workshop also considered difficulties created when an accidental introduction or unauthorized release of a potential BCA occurs.…”
Section: Introductionmentioning
confidence: 99%
“…With these results, an application to release the agent in the wild in Portugal was submitted in 2011. Following submission, a lengthy process ensued: Portuguese authorities informed the European Commission/ Standing Committee on Plant Health about the proposal and a decision was made to send it to the European Food Safety Authority (EFSA) for pest risk assessment (Jeger et al, 2016). Technical advice was received from EFSA in March 2015 and sent back to the Standing Committee on Plant Health.…”
Section: Introductionmentioning
confidence: 99%